Analyzing the Impact of Work-Life Balance, Creativity, and Job Stress on Employee Performance: The Mediating Role of Problem-Solving: English - Wiharni Az Lubis, Rizki; Siahaan, Elisabet; Sinulingga, Sukaria (Asian Multidisciplinary Research Journal of Economy and Learning, 2024)
This study aims to analyze the influence of work-life balance, creativity, and job stress on employee performance, with problem-solving as a mediating variable. The research was conducted on employees of PT. Bank Mandiri (Persero), Tbk, Unit CRC West Region I Sumatera 1, using a quantitative approach with the Structural Equation Modeling (SEM) method. Data were collected through questionnaires distributed to 160 respondents and analyzed using SmartPLS software. The results show that work-life balance and creativity have a positive and significant effect on employee performance, both directly and through problem-solving. Conversely, job stress has a significant adverse effect on employee performance, also mediated by problem-solving. The problem-solving variable plays an important role in bridging the relationship between work-life balance, creativity, and job stress with employee performance. This research provides practical implications for organizations to improve work-life balance, creativity, and employees' problem-solving abilities through flexible work policies, innovation training, and stress management programs. By focusing on the development of problem-solving skills, organizations can mitigate the effects of job stress and support employees in achieving optimal performance.